Discussion - Of Mr. Bolles' Paper on The Concentration of Gold and Silver in Iron-Bottoms (see p. 666) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
Edward Keller, Baltimore, Md. (communicatioin to the Secretary*):—It is pleasing to note the increasing amount of work on metallurgical problems that is being carried on by exact scientific methods, and the results of such labor issued by the laboratories of our universities. Without doubt, Mr. Bolles's paper will be welcomed by all progressive practitioners. Many of the results which Mr. Bolles presents to as are new; and I take exceptioil to a few minor points only. The first of his concluding remarks is as follows: "Mattes are not homogeneous, but are composed of distinct mineral entitier, and may be likened to igneous rocks, in which the mineral constituents fall out upon the lowering of the temperature and ensuing solidification." He quotes an introductory remark to a paper1 of mine, as follows: "The true chemical character of copper-mattes does not yet seem to have been definitely determined, i.e, it is still more or less of an open question whether they are true chemical compounds, or mixtures, such as igneous rocks." This quotation, taken alone, would convey the impression that Mr. Bolles's conclusion is entirely new. Had he quoted also another paragraph from my paper in question, it would be clear that he was, to a certain extent at least, anticipated. I take the liberty, therefore, to state the substance of my own work. In the paper referred to, I showed the existence of the phenomenon of liquation in mattes, and, continuing, said: " A more direct method to test whether a matte is a compound sulphide or a mixture of individual sulphides was attempted by applying hydraulic separation. A clean piece of matte was selected containing practically no magnetic oxide and of the following composition: Cu, 37.96; S, 24.45; Fe, 33.63; Zn, 1.25; Pb, 1.02 ; Sb, 0.26 ; As, 0.065 ; insoluble, 1.15 per cent. ; Ag, 26.7 ; Au, 0.04 oz. per ton. For such a test it is essential to select a chemically uniform piece, other-